Підвищення ефективності та надійності комбінованих суднових пропульсивних установок - Самонов, Сергій Федорович; Рак, Олександр Миколайович; Глазєва, Оксана Володимирівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Розглянуті шляхи підвищення ефективності використання енергії і зниження впливу на навколишнє середовище суднових дизельних пропульсивних установок на прикладі судна для транспортування контейнерів. Розроблений варіант модернізації пропульсивної установки, що забезпечує можливість збереження руху судна в особливих ситуаціях зі зменшеною потужністю за рахунок суднової електроенергетичної системи і валогенератора/двигуна. Проаналізовані переваги електроприводу гребного гвинта в складі синхронної машини і перетворювача частоти, що живляться від суднової електричної мережі, в порівнянні з головним дизельним двигуном, який працює з малою потужністю. Наведено оцінку ефективності використання електроприводу гребного гвинта за рахунок економії палива.

Purpose. Ensuring high propulsion performance in a wide range of modes by optimizing the control of technological processes of energy use. Ways to improve energy efficiency and reduce the environmental impact of diesel propulsion systems were considered. A Container ship was choose, as example. A ship`s combined type propulsion unit is equipped with a synchronous machine, which is installed in the propeller shaft line and performs the function of a shaft generator. Its use is possible only when the vessel main diesel engine operates with a power above 40% of the nominal. In economy modes and in special conditions of vessel movement with lower power, the efficiency of the working process in the main engine decreases, fuel consumption per unit of power and time, as well as harmful emissions, increases. That is, in the existing composition, the propulsion unit does not meet a modern requirements for efficiency and environmental friendliness, and the practice of its use is not flexible enough. Methodology. To confirm the economic feasibility of modernization and the use of PTH mode, mathematical modeling of electromechanical transients in the "Ship network - vectordriven synchronous motor - load" system was performed. Results. Improving the safety and survivability of the ship (PTH mode) due to the additional propeller independent of the main engine of the electric drive. Reducing fuel consumption and harmful emissions into the environment, which increases the EEIO (Energy Efficiency Operational Index) of the vessel. Originality. The developed version of the modernization of the propulsion installation provides running mode of the vessel in special situations with reduced power by means of using the shaft generator as a motor. To implement this option, the propulsion installation need to be equipped additionally with a hydraulic coupling, which is allow to disconnect the main engine from the propeller shaft and to change over to electrical driving of ship propeller. The advantages of the propeller electric drive as the synchronous machine and frequency converter which is supplied from the ship's electrical network, are analyzed in comparison with the main diesel engine operates with low power. The block diagrams of the electric drive with vector control are given. Practical value. When the vessel is moving at a low speed, switching to PTH mode saves fuel (up to 118 kg/h), and increases the completeness of its combustion, since diesel generators operate at optimal load, unlike the main engine, which in this case is extremely unfavorable for the machine.
Improving the efficiency and reliability of combined ship propulsions
Keywords: головний двигун; електронне управління; валогенератор; електродвигун; main engine; electronic control; shaft generator; electric motor